Interacción warfarina y aine - Armijos-Briones, Fernando Marcelo Marcelo; Gonza-Gonzaga, Lizbeth Judit; Navas-Mayorga, Camila Estefanía; Mena-Silva, Paola Andrea (Revista Arbitrada Interdisciplinaria de Ciencias de la Salud. Salud y Vida, 2021)
Interacción warfarina y aine